Adolescent Trajectories of Aerobic Fitness and Adiposity as Markers of Cardiometabolic Risk in Adulthood - Jackowski, S. A. (J Obes, 2017)
PURPOSE: The aim of this study was to investigate whether adolescent growth trajectories of aerobic fitness and adiposity were associated with mid-adulthood cardiometabolic risk (CMR). METHODS: Participants were drawn from the Saskatchewan Growth and Development Study (1963–1973). Adolescent growth trajectories for maximal aerobic capacity (absolute VO(2) (AbsVO(2))), skinfolds (SF), representing total body (Sum6SF) and central adiposity (TrunkSF), and body mass index (BMI) were determined from 7 to 17 years of age. In mid-adulthood (40 to 50 years of age), 61 individuals (23 females) returned for follow-ups. A CMR score was calculated to group participants as displaying either high or a low CMR. Multilevel hierarchical models were constructed, comparing the adolescent growth trajectories of AbsVO(2,) Sum6SF, TrunkSF, and BMI between CMR groupings. RESULTS: There were no significant differences in the adolescent development of AbsVO(2,) Sum6SF, TrunkSF, and BMI between adult CMR groupings (p > 0.05). Individuals with high CMR accrued 62% greater adjusted total body fat percentage from adolescence to adulthood (p=0.03). CONCLUSIONS: Growth trajectories of adolescent aerobic fitness and adiposity do not appear to be associated with mid-adulthood CMR. Individuals should be encouraged to participate in behaviours that promote healthy aerobic fitness and adiposity levels throughout life to reduce lifelong CMR.